Reliability and Norm Formation of Teacher’s Engagement Scale for Early Childhood Teachers in Indonesia - Azmi, Sunia Fauziah; Sulistyo Radikun, Tulus Budi (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
This study aims to validate the newly developed Teacher’s Engagement Scale, an instrument designed to measure teacher’s engagement in the classroom based on student engagement theory. The scale was constructed to address a gap in the existing tools, which mainly focus on teacher’s work engagement or job-related aspect. Therefore, this scale emphasizes behavioural, emotional, and cognitive dimensions of teacher’s engagement with their students. This study sample involved 499 early childhood educators in Indonesia. Reliability analysis of 23-item Teacher’s Engagement Scale initially indicates satisfactory overall and each dimension internal consistency with Cronbach Alpha’s (α = .90), and .85 for behavioural engagement, .70 for emotional engagement, and .80 for cognitive engagement. After removing one item each from emotional and cognitive engagement based on item rest correlation to analyse each items discriminative power, the reliability of overall, behavioural, emotional, and cognitive engagement became .91, .85, .75, and .85, respectively. Normative data were established by calculating z-scores, which revealed that the score distribution of Teacher’s Engagement Scale was normal with skewness value of −0.427 and kurtosis value of 2.88. These findings were used to create interpretative criteria for different engagement levels. This study highlights the need for improvements to the removed items and further validation of the scale through correlation with related constructs such as emotional intelligence and knowledge of good teaching practices.tudi ini bertujuan untuk mevalidasi Teacher’s Engagement Scale yang baru dikembangkan, yaitu suatu instrumen yang didesain untuk mengukur keterlibatan guru di dalam kelas berdasarkan teori keterlibatan murid. Skala ini dibuat untuk mengatasi kesenjangan dari alat ukur yang ada, dimana fokus utamanya lebih kepada keterlibatan kerja guru atau aspek yang berkaitan dengan pekerjaan. Maka, skala ini menekankan keterlibatan guru dengan murid mereka pada dimensi perilaku, emosional, dan kognitif. Sebanyak 499 guru anak usia dini di Indonesia terlibat sebagai sampel dalam studi ini. Analisis reliabilitas dari 23 aitem Teacher’s Engagement Scale awalnya menunjukkan konsistensi internal yang memuaskan secara keseluruhan dan pada setiap dimensi dengan Alpha Cronbach (α = .90), dan .85 pada keterlibatan perilaku, .70 pada keterlibatan emosional, dan .80 pada keterlibatan kognitif. Setelah menghapus satu aitem dari masing-masing keterlibatan emosional dan kognitif berdasarkan item rest correlation untuk menganalisis daya diskriminasi setiap aitem, reliabilitas keseluruhan, perilaku, emosional, dan kognitif secara berurutan menjadi .91, .85, .75, dan .85. Norma diperoleh dengan menghitung z-scores, yang menunjukkan bahwa distribusi skor dari Teacher’s Engagement Scale ialah normal dengan nilai skewness −0.427 dan nilai kurtosis 2.88. Hasil ini digunakan untuk membuat kriteria interpretatif untuk tingkat keterlibatan yang berbeda-beda. Studi ini menyarankan perlu adanya perbaikan pada aitem-aitem yang dihapus dan validasi skala ini lebih lanjut dengan konstruk yang berkaitan seperti kecerdasan emosional dan pengetahuan mengenai praktik mengajar yang baik.